Catch her when she falls : a novel - Buccola, Allison (Random House, 2022)
"Ten years ago, my boyfriend killed my best friend. At least that's what Micah has believed ever since her high school sweetheart, Alex, was convicted of murdering her best friend, Emily. A decade later, Micah has finally moved on from the unforgivable betrayal and loss. Now the owner of a bustling coffee shop in her small hometown in Pennsylvania, she's happily coupled up with another old high school friend, the two having bonded over their shared sorrow. But when reminders of her past begin appearing at her work and home, Micah begins to doubt what she knows about Emily's death. Questions raised on a true crime blog and in an online web sleuthing forum force her to reexamine her memories of that fateful night. She told the truth to the investigators on the case, but was there another explanation for Emily's murder? A stranger in the woods. An obsessive former classmate. Or the internet's favorite suspect: Joshua, Emily's outcast younger brother who hasn't been seen since his sister's death. As Micah delves deeper into the case--and her memories of the night--she feels her grip on reality loosening, her behavior growing more and more secretive and unhinged. And when everything spills over into a violent altercation, she flees to the secluded Massachusetts beach town where she believes Joshua is hiding out. As she races to find him, and the missing pieces of that night ten years ago, Micah grapples with how things have gone so wrong and wonders how she, too, might disappear"--